2009
DOI: 10.1590/s1413-70542009000400013
|View full text |Cite
|
Sign up to set email alerts
|

Produção de matéria seca, teor e acúmulo de silício em cultivares de arroz sob doses de silício

Abstract: RESUMOO efeito do silício (Si) na produção de matéria seca de arroz, teor e acúmulo de Si foi avaliado sob condições de casa-de-vegetação. O delineamento experimental foi o inteiramente casualizado em esquema fatorial 5 x 2 com 4 repetições. Os tratamentos foram 5 doses de Si (0; 0,25; 0,50; 0,75 e 1,00 g dm -3 ) e 2 cultivares de arroz (Conai e Curinga). A aplicação de Si não afetou os componentes de crescimento e produção, com exceção da matéria seca de raiz. Houve um acréscimo da matéria seca de raiz sob ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…However, based on the mean comparison analysis (table 2), it was observed that si rates did not influence dry matter yield of the aerial part (DmaeP), roots (Dmrt), and total dry matter yield (tDmy). Korndörfer et al (2010), faria Junior et al (2009), and mauad et al (2003 found no significant effects of si fertilization either on dry matter yield in pasture and rice. this is due to the fact that si is related to a structural function, not to growth processes such as cell elongation and multiplication.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, based on the mean comparison analysis (table 2), it was observed that si rates did not influence dry matter yield of the aerial part (DmaeP), roots (Dmrt), and total dry matter yield (tDmy). Korndörfer et al (2010), faria Junior et al (2009), and mauad et al (2003 found no significant effects of si fertilization either on dry matter yield in pasture and rice. this is due to the fact that si is related to a structural function, not to growth processes such as cell elongation and multiplication.…”
Section: Resultsmentioning
confidence: 98%
“…this reduces transpiration and increases the mechanical resistance of the leaves against fungal infection and insect attacks. in many studies (faria Junior et al,2009;mauad et al, 2011), no positive effect of si was verified, even when applied to si-poor soils and to crops under some type of stress; maybe because the si leaf contents were not very different from stressfree plants fertilized with the element (mauad et al, 2011). this discrepancy in results could be related to genetic factors, i.e., differences between cultivars with regard to their uptake capacity at low si availability and/or to utilize the absorbed element with higher efficiency.…”
mentioning
confidence: 99%
“…Os resultados do presente estudo estão de acordo com os obtidos para café (Faria Júnior et al, 2009), jambu (Borges et al, 2010 e rúcula (Guerrero et al, 2011), em que também não se observou influência nos componentes de crescimento. Porém, são discordantes dos obtidos para morango (Figueiredo et al, 2008), soja (Moreira et al, 2010) e batata (Soratto et al, 2012), nos quais houve aumento de massa seca e maior translocação de fotoassimilados, quando as plantas foram tratadas com Si.…”
Section: C Bunclassified
“…Existem, na literatura, resultados promissores com a utilização de Si na agricultura, para a cultura do arroz, tais como aumento do número de folhas, massa seca de plantas e número de espiguetas por panícula, melhor formação e qualidade da casca dos grãos, maior altura de plantas e maior teor e acúmulo na parte aérea da planta (Lopes 1997, Korndörfer et al 1999, Gong et al 2003, Bittencourt et al 2004, Tokura et al 2007), entretanto, outros autores (Bar-bosa Filho et al 1998, Carvalho 2000, Mauad et al 2003 encontraram resultados diferentes, dependendo das doses de Si aplicadas, tipo de cultivar de arroz e solo, bem como condições ambientais.…”
unclassified